Anaesthesia with diethyl ether impairs jasmonate signalling in the carnivorous plant Venus flytrap (Dionaea muscipula) - Pavlovič, Andrej (Ann Bot, 2020)
BACKGROUND AND AIMS: General anaesthetics are compounds that induce loss of responsiveness to environmental stimuli in animals and humans. The primary site of action of general anaesthetics is the nervous system, where anaesthetics inhibit neuronal transmission. Although plants do not have neurons, they generate electrical signals in response to biotic and abiotic stresses. Here, we investigated the effect of the general volatile anaesthetic diethyl ether on the ability to sense potential prey or herbivore attacks in the carnivorous plant Venus flytrap (Dionaea muscipula). METHODS: We monitored trap movement, electrical signalling, phytohormone accumulation and gene expression in response to the mechanical stimulation of trigger hairs and wounding under diethyl ether treatment. KEY RESULTS: Diethyl ether completely inhibited the generation of action potentials and trap closing reactions, which were easily and rapidly restored when the anaesthetic was removed. Diethyl ether also inhibited the later response: jasmonic acid (JA) accumulation and expression of JA-responsive genes (cysteine protease dionain and type I chitinase). However, external application of JA bypassed the inhibited action potentials and restored gene expression under diethyl ether anaesthesia, indicating that downstream reactions from JA are not inhibited. CONCLUSIONS: The Venus flytrap cannot sense prey or a herbivore attack under diethyl ether treatment caused by inhibited action potentials, and the JA signalling pathway as a consequence.